2017
DOI: 10.21475/poj.10.02.17.pne386
|View full text |Cite
|
Sign up to set email alerts
|

Mineral deficiencies influence on tomato leaves: pigments, hydrogen peroxide and total phenolic compounds contents

Abstract: The detection of hydrogen peroxide, chlorophyll pigments, anthocynin, carotenoids, total phenolic compounds and lipid peroxidation levels as potential stress signaling molecules in tomato (Lycopersicon esculentum Mill.) leaves in response to specific mineral deficiency were studied. The stress signaling molecules were measured in the plant leaves at different growth time points cultured in specific mineral deficient nutrient solutions. The results showed that hydrogen peroxide was significantly increased after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…Similar to most of our results, it was reported that the levels of endogenous anthocyanins in foliage are stimulated by different abiotic factors 10 , 19 . However, contrast results of elevated anthocyanin content in response to long-term exposure (6 weeks) to temperature 20 or to the synergetic effect of high temperature and duration of cultivation 21 was reported.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar to most of our results, it was reported that the levels of endogenous anthocyanins in foliage are stimulated by different abiotic factors 10 , 19 . However, contrast results of elevated anthocyanin content in response to long-term exposure (6 weeks) to temperature 20 or to the synergetic effect of high temperature and duration of cultivation 21 was reported.…”
Section: Discussionsupporting
confidence: 93%
“…Under the latter stressor, anthocyanin and carotenoids contents, MDA and protein content decreased, while under low temperature anthocyanin and carotenoids contents increased and the other indices were decreased. www.nature.com/scientificreports/ Similar to most of our results, it was reported that the levels of endogenous anthocyanins in foliage are stimulated by different abiotic factors 10,19 . However, contrast results of elevated anthocyanin content in response to long-term exposure (6 weeks) to temperature 20 or to the synergetic effect of high temperature and duration of cultivation 21 was reported.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, the ROS–antioxidant balance within different compartments of photosynthetically active cells is a highly dynamic system (temporal as well as spatial) and might therefore not be adequately reflected by static measurements. For instance, studies that investigated time courses of ROS accumulation and enzyme activities during the onset of Mg deficiency found different antioxidant enzyme activities as well as ascorbate, glutathione or ROS concentrations depending on the time after the onset of Mg deficiency (Anza et al, 2005; Alsharafa, 2017; da Silva et al, 2017). Hence, contradictory results might also be explained by different experimental setups and further dependencies e.g., on the sampling date or day time of sampling or interrelations to other metabolic cycles such as nitrogen assimilation and photorespiration are likely.…”
Section: Discussionmentioning
confidence: 99%
“…The importance for measuring the photosynthetic pigment contents may be to infer some physiological signals that could be extensively employed in stress detection [ 47 ]. Moreover, chlorophyll parameters also provide an indication of nutritional status [ 48 ]. In addition, the accumulation of carotenoids is regarded to suppress the oxidation caused by oxidative stress [ 49 ].…”
Section: Resultsmentioning
confidence: 99%